Classification of living beings by elementary school students: a proposal for the development of scientific skills - Andrea Inês Goldschmidt; Ariadne de Freitas Leonardi; Carolina Rangel; Geovane Bernardi; Maira dos Santos Silveira; Sabrina Antunes Ferreira (ACTIO: Docência em Ciências, 2019)
The article presents a pedagogical experience developed with students from the early years of elementary school of a public school in the city of Palmeira das Missões, RS, during the process of teaching the biological classification of living beings that aimed to highlight the knowledge. students' daily life on the form of organization and classification of the diversity of living organisms, allowing to evaluate and discuss the differences in relation to biological classification, without, however, proposing the exclusion of one knowledge because it considers the other the correct one. In addition, provide opportunities for students to develop scientific skills associated with observing, organizing, classifying, proposing models, arguing and reporting orally. The research had as investigative instrument the construction of posters, presenting a biological classification system from the observation of 36 images (photographic) containing different specimens of animals, plants, fungi, viruses, bacteria and protozoa. Thus, the students were observed in each group by one of the researchers and in addition to organizing the classification system, should establish criteria for them. In all, sixteen groups were formed, which organized sixteen rating posters, these were collected and analyzed. The results showed that the students classified the animals according to their environment, taxon and observable characteristics. Habitat classification was found to decrease with advancing school years, with less emphasis on observation. As for plants, it was observed that most students have an anthropocentric utilitarian view, especially the role of these organisms in human food. Regarding microorganisms, it was noted that students have a reductionist and often erroneous view of these beings, classifying them as minor causes of disease. Comparing the years of education, it was found that the students of the first years (first, second and third) showed better development of observation and as they get older, the classification was more memoristic, and based on the rates and classifications present in Didatic books. These results show that developing students' scientific skills is very important.